National Question in the U.S. and Canada’s Domestic Politics: Conclusions from the Comparative Analysis - Олег Козачук (Історико-політичні проблеми сучасного світу)
The conclusions of the research «National Question in the U.S. and Canada’s Domestic Politics: Comparative Analysis» are proposed for consideration here. For the first time in Ukrainian political science, a cross-national comparison of the USA and Canada in the context of the analysis of the national question was carried out. Namely, its essence was clarified, the peculiarities of multicultural practices in the USA and Canada (cultural pluralism and multiculturalism) were analyzed, and an analysis of ethno-racial discrimination and ethnic mobilization was conducted. The research methodologically conceptualized and developed a comparative political study of interethnic interactions with the use of a research strategy for comparing most similar systems (for example, the USA and Canada). The case study method has been substantiated and applied, involving the method of structural and focused comparison as a tool of cross-national research (for example, the USA and Canada), and also proved that the method can be effective in comparative political science. In the research, the indexation of immigration policy was conceptualized, and a scientific apparatus (a logical sequence of conceptualization, measurement and aggregation) for further cross-national studies in which the object is the national question in general and the migration policy in particular was developed. The theoretical results of the research can be used for the further design of models of binary implicit comparison of similar states. The case study method has not yet been properly applied in Ukrainian political science; therefore, the method proposed by the author for a structured and focused comparison of cases can be useful for both scholars and practitioners when comparing phenomena and processes. The author proposed the concept and design of a study of the already forgotten issues of the national question, which has been proven not to be outdated even in such advanced polyethnic states as the USA and Canada. The scientific results obtained by the author can be used by subjects of internal policy, first of all in the practice of public authorities. The proposed method of indexing immigration policy can serve scholars, legislators, government officials, and employees of the executive authorities to carry out cross-national and/or cross-temporal comparisons.